Organizational commitment and its relationship to administrative transparency An applied study at the Brega Oil Marketing Company in the city of Benghazi (Economic studies journal, 2021)
AbstractEstimating the GDP Gap in the Libyan Economy The study aimed to identify the degree of organizational commitment and its dimensions (emotional commitment, continuity commitment, normative commitment) and its relationship to administrative transparency in the Brega Oil Marketing Company in Benghazi. The study population consisted of all the directors of the middle departments of(116) managers, the researcher studied it completely using the comprehensive inventory method, and the statistical packages program (spss) was used in analyzing the data, and the study reached many results, the most important of which are: The degree of commitment to the organization has It was high, and the level of administrative transparency was average, as well as the existence of a direct correlation between organizational commitment and its dimensions and administrative transparency, as well as the existence of a direct correlation between the dimensions of organizational commitment (emotional commitment, continuity commitment, normative commitment), and administrative transparency, and the study presented a group of Recommendations that will hopefully contribute to enhancing the degree of organizational commitment and improving the level of administrative transparency in Al- Brega Company To market oil in Benghazi.
Keywords: Organizational Commitment; Administrative Transparency; Brega Oil Marketing Company